On Belonging: Children Respond to Trump through Play and Imagination - Price, Emily Claire; Jurow, A. Susan (Radical Teacher, 2018)
In this article, we describe the critical role of play in exploring issues of equity with young children. We provide examples of how we designed for play-based explorations of privilege and power in a low-income afterschool program with majority Latino students in the months before, during, and after the election of Donald Trump. In examining the play that resulted, we describe how the children explored themes of identity and belonging as a means of interrogating, interrupting, and responding to Trump’s characterizations of Mexicans in particular.